El derecho a la estabilidad laboral reforzada de los servidores públicos en procesos de supresión de puestos en los Gobiernos Autónomos Descentralizados - Asqui Bravo, Marco Alexander (2024)
Ecuador, a country that guarantees rights and justice, must ensure full compliance with what is prescribed in our Constitution; since it is the law with the highest hierarchy in the country, no one can go against it, nor can they violate rights established in the Constitution. Likewise, these rights have been obtained through the State since our conception. We also have rights coming from binding sentences; among all those rights, we find the right to reinforced job stability of public servants, which will be very important for our research, in addition to the right to due process, the right to legal certainty, the right to adequate judicial protection and the right to defense. This investigation will analyze and identify whether there is a violation of rights framed in our Constitution when carrying out a process of eliminating positions in a public institution to public servants who enjoy reinforced job stability, such as those people who have a disability, people with catastrophic illnesses or orphan diseases, pregnant or breastfeeding women or, in turn, substitutes or caregivers for a person who suffers from those above. To determine the proposed objectives, a field investigation will be carried out, through which real cases related to the research problem will be accessed. In addition, the synthetic analytical method will be used, which will allow the identification and analysis of legal norms, doctrine, and jurisprudence regarding the violation of the right to job security, which will be reinforced by the elimination of positions for public servants. These rigorous research methods will ensure the credibility and transparency of our findings.